Preharvest Calcium sprays were not always needed to improve fruit quality of 'Gala'apples in Brazil - Ervani P.R.* (2008)
Calcium sprays have normally improved both the quality and the storage life of apples throughout the world because Ca helps to prevent many fruit disorders and that taken up from the soil does not often reach the fruit in adequate amounts. Since the efficacy of Ca sprays varies according to soil, apple cultivar, and weather conditions, this study was carried out from 1998 to 2004, in the Southern of Brazil, in order to assess the effect of Ca sprays on the quality and storability of 'Gala' fruits. The experiment was set up in an orchard planted in 1988, on a density of 1234 trees/ha. Treatments consisted of 0, 4, 8, and 12 annual sprays of 0.5% CaCl2 regularly distributed 30 days after petal fall until one week before harvest. Fruits of the same size and maturity level were annually analyzed at harvest and after five months of conventional cold storage (-1°C and 90-95% of RH). In five out of six seasons, fruits from all treatments were free of any physiological disorder, and Ca sprays had no effect on leaf composition and on any fruit attribute (soluble solids, titratable acidity, starch pattern index, flesh firmness, and concentrations of N, K, Ca and Mg). In the season of 2000/ 2001, however, when yield was 18 t ha-1 and fruits had an average weight of 175 g, the incidence of bitter pit plus lenticel blotch pit on stored fruits was 24% in the treatment with no calcium sprays and it decreased up to 2% in that with 12 sprays. Two seasons later, yield was also low (25 t ha-1) and fruits were large (168 g each), but they did not show any physiological disorder regardless of the number of Ca sprays. It seems that the incidence of Ca related disorders in 'Gala' apples grown on limed soils in Brazil with no excess of any nutrient only occurs on seasons with low crop yield, as a result of large fruits and a high leaf/fruit ratio, associated with some unknown environmental conditions.